The Influence of Compensation and Company Reputation on Gen Z's Decision to Choose to Work as an Assistant in Oil Palm Plantations With Work-Life Balance as a Moderation Variable - Hadi, Danang; Novianti, Fawzia; Seswandi, Agus (Jurnal Ilmu Sosial Mamangan, 2025)
This study aims to determine the influence of compensation and company reputation on Gen Z's decision to choose to work as an assistant in oil palm plantations with work-life balance as a moderation variable. The type of research used is quantitative research with 2 (two) data sources, namely primary data consisting of questionnaire data and secondary data consisting of journals, articles and others. This research consists of 3 (three) variables, namely exogenous variables consisting of compensation (X1) and company reputation (X2), endogenous variables consisting of decisions to choose work (Y) and moderation variables consisting of work life balance (Z). This study was conducted in February – April 2025 on 106 Gen Z respondents who worked as assistants in oil palm plantations. Data analysis using the SmartPLS application with 3 (three) analyses, namely outer model analysis, inner model analysis, and bootstrapping or hypothesis analysis. The results of the study obtained from the analysis of the outer model show that all indicators or items have met the requirements for validity and realism and no multicollinearity between indicators was found. Analysis of the inner model showed that the structural model in the study was proven to be stable without multicollinearity. The bootstrapping analysis or hypothesis shows that compensation and company reputation are proven to have a significant influence on Gen Z's decision to choose to work as an assistant in oil palm plantations, while Work-Life Balance does not play a moderator role in the relationship between these two variables and Gen Z's decision to work as an assistant in oil palm plantations.